The Sociological Perspective Revisited - Rodger A. Bates (Journal of Public and Professional Sociology)
In the 1950s, sociology was committed to the development of a set of basic concepts for advancing the discipline. Heavily influenced by structure-functionalism, sociology focused on general and mid-range theories in seeking to understand and explain society. By the 1960s this perspective was challenged by the emergence of modern conflict theory with its emphases on race, class and gender and the consequences of inequality. However, with the success of the social movements of the latter half of the century, sociology embraced deconstructionism. As a consequence of this trend, sociology increasingly embraced empathy and personal experience over systemic understanding and scientific inquiry. Today, the relevance of sociology as a tool of understanding is being challenged by the sociology of me. “The Sociological Perspective Revisited” describes this transformation and the challenges it creates for the future of the discipline.